Composition and distribution of macrobenthos in the Bay of Sechura, Piura, Peru - Yupanqui, Williams (2007)
It was analyzed the spatial distribution of the benthic macrofauna of the Bay of Sechura (5°12’ - 5°50’S and 81°12’ - 80°51’W) right after the end the 1997-98 El Niño. Temperature, dissolved oxygen, sand content (%), exhibited a decreasing trend from shallow to deep stations, while or- ganic matter content, equitability and diversity increased with depth. The Polychaeta were the most abundant taxonomic group (81 %). The composition was very heterogenous at shallower depths (5 – 11 m), and the polychaete Polydora socialis tended to dominate in sandy and rocky bottoms with 54 %. Polychaetes from the family Capitellidae (17 %) dominated at intermediate depths (21 – 35 m), while the spionid polychaete Paraprionospio pinnata (27 %) was the dominant species at deeper locations (42—72 m). The dominant feeding guilds were surface deposit feeders and interface feeders. In comparison with information collected at the onset of El Niño 1997-98, there were differences in the composition of dominant species, especially at intermediate depths, but there were not found signifi cant differences in the community parameters.